Implementation Of Medan Mayor Regulation Number 26 Of 2024 Concerning Guidance For Implementing Subscription Parking Services On The Road Side From A State Constitutional Law Perspective - Kiki Fadhilah; Tamaulina Br. Sembiring; Abdul Rahman Maulana Siregar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
One of the public policies in the form of regional head regulations of the Regent/Mayor is the Medan City Mayor Regulation Policy (Perwal) Number 26 of 2024 concerning the Implementation of Subscription Parking on Public Roadsides. The regulation implements a roadside subscription parking system in the capital city of North Sumatra Province by subscription starting July 1, 2024. The amount of the subscription parking fee is IDR 90,000/year for two-wheeled vehicles, IDR 130,000/year for four-wheeled vehicles, and IDR 168.000,000/year for trucks/buses.This study uses the Empirical Juridical Type of legal research method, namely research that focuses on examining theory and practice in positive law. is research that places law as a social phenomenon. The data collection method used is by interview. This study refers to primary and secondary data (field and library data). The public supports the subscription parking program to maximize the acquisition of Regional Original Income (PAD) from the parking sector, but the process, substance and implementation must not violate the rights of citizens, especially if it conflicts with applicable laws and regulations.